Solve for \( u \). \[ \begin{array}{l}0.2 u=-0.5+3(0.8 u+0.9) \\ u=\square\end{array} \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve for \( u \), we start with the equation: \[ 0.2 u = -0.5 + 3(0.8 u + 0.9) \] First, we simplify the right side of the equation: \[ 0.2 u = -0.5 + 3 \times 0.8 u + 3 \times 0.9 \] \[ 0.2 u = -0.5 + 2.4 u + 2.7 \] \[ 0.2 u = 2.2 + 2.4 u \] Now, we want to isolate \( u \). Next, we can combine like terms: \[ 0.2 u - 2.4 u = 2.2 \] \[ -2.2 u = 2.2 \] To solve for \( u \), we divide both sides by -2.2: \[ u = \frac{2.2}{-2.2} = -1 \] Thus, the solution is: \[ u = -1 \]